Fuzzy Logic Based Simulation for Modeling of Sustainable Marketing Policy for Modern Rice Mills in Odisha - Er. Banshari Rath; Bishnu Prasad Mishra; Prof B. K. Mangaraj (International Journal of Supply Chain Management, 2012)
Rice is consumed by 50 per-cent of the world population. It has a strong market demand as the starch and fibers of rice has been reported to be superior to that of wheat. Orissa produces small, medium and long grain rice traditionally which has commercial importance. The strategy for modernization of the traditional technology based rice mills has to be planned. Up-gradation of rice mills must be done by high tech modern technology so that the rice thus produced can be marketed globally at a premium price. Artificial intelligence based fuzzy logic has been used in this model to determine the numbers of rice mill required to be programmed under proposed symbiotic development program over time. The parameters like rice production, variation in production, paddy grain type, production technology and capacity of the rice mill and geographic boundary have been considered to simulate this strategy. Implementation of this strategy can bring a sea change in the economic status of farmers of Odisha, India engaged in production of paddy which has international acceptance. The suitable climatic factor can be used for growing different paddy varieties and commercially manage it for more profit through value addition and positioning the product in global market.